2019
DOI: 10.1093/jscr/rjy335
|View full text |Cite
|
Sign up to set email alerts
|

A nail in the appendix, accidental discovery on an asymptomatic patient

Abstract: Inadvertent ingestion of foreign bodies is a common condition within clinical practice. It rarely produces any symptoms. The diagnosis is difficult since most patients do not recall having swallowed any object. Needles, pins, keys, nails and bones are among the most commonly ingested foreign bodies. Severe complications are uncommon, but if present they can put patients’ lives at risk. Although extremely rare, the ingested foreign body may end lodging in the appendix, posing a challenge for the clinical team. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Appendiceal symptoms are a red focus in the clinical evaluation after the ingestion of objects; however, linking foreign body ingestion with appendiceal symptoms is usually difficult, especially in psychiatric patients with poor self-care or lack of control of their underlying pathology. Likewise, asymptomatic patients may even have forgotten the ingestion by not giving importance to it, missing an important pillar in the presumptive etiological diagnosis [4,11,12]. It has been reported that up to 29% of retained appendiceal foreign bodies are asymptomatic [11].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal symptoms are a red focus in the clinical evaluation after the ingestion of objects; however, linking foreign body ingestion with appendiceal symptoms is usually difficult, especially in psychiatric patients with poor self-care or lack of control of their underlying pathology. Likewise, asymptomatic patients may even have forgotten the ingestion by not giving importance to it, missing an important pillar in the presumptive etiological diagnosis [4,11,12]. It has been reported that up to 29% of retained appendiceal foreign bodies are asymptomatic [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thankfully, the intestine has an intrinsic ability to protect itself from perforations; when the bowel wall is affected and punctured, the mucosa enlarges the bowel wall at the point of contact, allowing easier pass of that object [ 6 ]. Yet if the object is metallic, sharp, stiff or pointed, it is more likely to cause complications such as an abscess, adhesions or fistulas [ 2 , 7 ]. In addition, when a foreign body perforates the bowel wall, it can follow several routes; it can lie trapped to the bowel wall, lie close to the perforation site, or migrate distally and perforate it again [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet if the object is metallic, sharp, stiff or pointed, it is more likely to cause complications such as an abscess, adhesions or fistulas [ 2 , 7 ]. In addition, when a foreign body perforates the bowel wall, it can follow several routes; it can lie trapped to the bowel wall, lie close to the perforation site, or migrate distally and perforate it again [ 4 , 7 ]. In our case, the needle was found piercing the colonic wall but was not free in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Cases were reported from 25 countries, with 18 cases reported from USA [ 8 - 19 ], seven from UK [ 5 , 20 - 25 ], five from Japan [ 26 - 30 ] and Korea [ 31 - 35 ] each, three from the Netherlands [ 36 - 38 ] and from Turkey [ 39 - 41 ]. Australia [ 42 , 43 ], Ecuador [ 44 , 45 ], Italy [ 46 , 47 ] and Taiwan [ 48 , 49 ] each had two cases while the rest of the following reported only one case: Austria, Cameroon, China, Croatia, France, Germany, Iran, Ireland, Kuwait, Morocco, New Zealand, Peru, Saudi Arabia, Singapore and Spain [ 50 - 64 ]. Table 1 illustrates characteristics of case reports (author, year, country, age and gender).…”
Section: Reviewmentioning
confidence: 99%